Relationship Between the Estimated Breeding Values for Litter Traits at Birth and Ovarian and Embryonic Traits and Their Additive Genetic Variance in Gilts at 35 Days of Pregnancy - Da Silva, Carolina L. A.; Mulder, Han A.; Broekhuijse, Marleen L. W. J.; Kemp, Bas; Soede, Nicoline M.; Knol, Egbert F. (Frontiers in Genetics, 2018)
We investigated 1) the relationship between the estimated breeding values (EBV) for litter traits at birth and ovulation rate (OR), average corpora luteal weight, uterine length and embryonic survival and development traits in gilts at 35 days of pregnancy by linear regression, 2) the genetic variaance of OR, average corpora lutea weight, uterine length and embryonic survival and development traits at 35 days of pregnancy and 3) the genetic correlations between these traits.. Landrace (n = 86) and Yorkshire x Landrace (n = 304) gilts were inseminated and slaughtered at 35 days of pregnancy. Ovulation rate (OR) was assessed by dissection of the corpora lutea (CL) on both ovaries. Individual CL were weighed and the average CL weight calculated. The number of embryos (total and vital) were counted and the vital embryos were individually weighed for calculation of within litter average and standard deviation (SD) of the embryo weight. Length of the uterine implantation site of the vital embryos was measured and the average per gilt calculated. Results suggests that increasing the EBV for total number of piglets born would proportionally increase OR and number of embryos, while decreasing the average CL weight. On the contrary, increasing the EBV for average piglet birth weight and for within litter birth weight standard deviation would increase the average CL weight. There was no relationship between the EBVs for BW and for BWSD and vital embryonic weight at 35 days of pregnancy. Ovulation rate, average CL weight, number of embryos, average weight and implantation length of the vital embryos had all moderate to high heritabilities, ranging from 0.36 (± 0.18) to 0.70 (± 0.17). Thus, results indicate that there is ample genetic variation in ovulation rate, average CL weight and embryonic development traits. This knowledge could be used to optimize the balance between selection for litter size, average piglets birth weight and within litter birth weight uniformity.